Encrypted e-commerce product - BIBLE, JR. ROBERT; BURNETT MARK STEVEN (2010)
A system for conducting a financial transaction in e-commerce on the internet includes objects prepared by a seller and a buyer. The seller's object includes a clear text header file (advertisement), an encrypted overhead file which contains verification data pertaining to the financial transaction, and an encrypted content file containing the subject matter for sale by the seller. With a purchase solicitation from the buyer, an overhead key can be used by a transaction agency to ensure there is a compliance between the purchase solicitation and the verification data of the overhead (from seller's object). Next a revelation key is provided to give the buyer access to the content when such compliance has been ensured.